As luzes da cidade acesas e o apagamento da Gestão Democrática: uma análise da revisão do Plano Diretor Municipal de Guarapuava, PR 2016/2026 - Silva, Alisane da (2021)
In dark times, when successive attacks on the rule of law to democracy occur, when old mechanisms are being reheated to silence, to erase the social participation of public management, science, the university have a fundamental role in denouncing, researching, development of knowledge to maintain democratic principles. In this sense, this dissertation seeks to discuss the Democratic Management of the City, from the analysis of the revision of the Master Plan for the 2016/2026 decade of the city of Guarapuava, PR. The methodology used was Qualitative Research, since the purpose of this dissertation is to specifically analyze a process within Urban Policy, the process of Democratic Management of the City from the perspective of the existence and quality of this participation. The research was structured in three parts: the first review of literature focused on Urban Policy in Brazil, as well as local regulations, specific literature focused on the theme; the second stage turned to the collection of secondary data from the Municipal Secretariat of Housing of Urbanism and Guarapuava (SMHU) since the beginning of the disclosure of the elaboration of the 2016/2026 Master Plan, its planning and implementation until 2020, being: a) Reports , minutes of hearings, planning meetings, publicity documents for the acts calling for meetings and hearings; b) Resolutions on the places of advertising, communication channels for calling the public, time period for public calling; c) Resolutions on the time allocated for the analysis of proposals; d) Data on the places where the hearings were held, segments of the participants, proposals presented by the participants and their segments if such proposals were accepted or not) Reports from the communities (associations of residents or groups) about their reality, the point of view of who lives in the neighborhood and knows its territory. The search for media content produced by local newspapers about the Master Plan, matters related to public hearings, neighborhood meetings was included in the data collection methodology; The third stage included the analysis of data related to social participation, the reading of the minutes of hearings, the attendance lists to find out which public and private actors participated, the processes of calling for participation, the dissemination channels. At this point, he entered the complexity of the participatory construction of the city, in the fabric of the articulations that may or may not promote its Democratic Management. It is concluded by the obtained data, that the construction of the city has been thought by few, by the entrepreneurs, owners of real estate, great investors, who propose legislation that benefit themselves, that do not consider the local peculiarities and affect the collectivity. That the exercise of social participation was compromised in this process by several factors, namely: the low disclosure of the revision of the Master Plan, the precarious methodology of participation, the lack of awareness of the importance of the document, the lack of time for discussing proposals. In addition, the antidemocratic performance of the municipal executive and legislature was seen in the approval of laws subsequent to the revision of the Master Plan, without going through the Master Plan Council and without popular consultation according to the guidelines of the City Statute on Democratic Management.